100k views
5 votes
If f(x)=x/4-3 and G(x)=4x^2+2x-4 find (f+g)(x) can someone do this step by step? please.

User Mieka
by
5.7k points

2 Answers

4 votes
You are really just adding the two functions together to create a new function.

x/4 -3+4x^2+2x-4 (making everything have a common denominator of 4 we get:

(x-12+16x^2+8x-16)/4 combine like terms in numerator

(16x^2+9x+4)/4
User Carry
by
6.1k points
3 votes

Answer:

The value of (f+g)(x) is
4x^2+(9x)/(4)-7.

Explanation:

The given functions are


f(x)=(x)/(4)-3


g(x)=4x^2+2x-4

We have to find the value of (f+g)(x).


(f+g)(x)=f(x)+g(x)


(f+g)(x)=(x)/(4)-3+4x^2+2x-4

Combine like terms.


(f+g)(x)=4x^2+((x)/(4)+2x)+(-3-4)


(f+g)(x)=4x^2+(x+8x)/(4)+(-7)


(f+g)(x)=4x^2+(9x)/(4)-7

Therefore the value of (f+g)(x) is
4x^2+(9x)/(4)-7.

User RobbieCanuck
by
6.8k points